Emplacement age of the Markagunt gravity slide in southwestern Utah, USA. (23rd November 2022) - Holliday, McKenna E.; Rivera, Tiffany; Jicha, Brian; Trayler, Robin B.; Biek, Robert F.; Braunagel, Michael J.; Griffith, W. Ashley; Hacker, David B.; Malone, David H.; Mayback, Danika F.
Abstract: The Markagunt gravity slide (MGS) is a large‐volume landslide in southwestern Utah that originated within the Oligocene‐Miocene Marysvale volcanic field. Gravity slides are single emplacement events with long runout distances and are now recognized as a new class of volcanic hazard. Accumulation of volcanic material on a structurally weak substrate along with voluminous shallow intrusive events led to collapse. Here, 40 Ar/ 39 Ar data for landslide‐generated pseudotachylyte, the landslide‐capping Haycock Mountain Tuff and the deformed Osiris Tuff are combined with a Bayesian age model to determine an emplacement age of 23.05 + 0.22/−0.20 Ma for the MGS. The results suggest a lag time of <200 kyr between the caldera‐forming eruption of the Osiris Tuff, additional buildup of the unstable volcanic pile and subsequent mass movement.